Pan in A Brand New Key - Joseph, Terry (Express)
Pan Trinbago President Owen Serrette states that if pan is a musical instrument, then its players should be musicians as defined and understood in international terms, they must be able to read and write music. A large percentage of pan players will be reading their notes in order to learn the Panorama tune.
Keywords: Steel bands (Music) -- Study and teaching -- Trinidad and Tobago; Music -- Instruction and study -- Trinidad and Tobago; Musicians -- Trinidad and Tobago; Steel drum (Musical instrument) -- Instruction and study -- Trinidad and Tobago